Different diuretic dose and response in acute decompensated heart failure: Clinical characteristics and prognostic significance. (1st December 2016) - Palazzuoli, Alberto; Testani, Jeffrey M.; Ruocco, Gaetano; Pellegrini, Marco; Ronco, Claudio; Nuti, Ranuccio
Abstract: Background: The question regarding the correct balance between optimal loop diuretic dose administration and best modality is under debate as well as the exact relation existing between congestion and renal dysfunction. We sought to evaluate the effects of different diuretic modalities (low [LD] versus high dose [HD]) and dose administration on decongestion, Worsening renal function (WRF) and outcome. Methods: We retrospectively analyzed data of DIUR-HF study matching for LD vs HD (cut off 125 mg/day), and diuretic efficiency (DE) (weight loss/40 mg daily of furosemide). We also evaluated WRF rate (creatinine increase during hospitalization ≥ 0.3 mg/dl or estimated glomerular filtration rate (eGFR) reduction ≥ 25%) together with decongestion. Results: HD patients (n.55) were older, more frequently affected by diabetes and chronic kidney disease (CKD) and demonstrated higher rate of inhospital WRF (65% vs 29% p = 0.001) and 180-days adverse events (70% vs 23% p < 0.001) respect to LD patients (n.41). Patients with low DE showed a higher 180 days adverse events rate than higher DE patients (p = 0.02). Univariate and multivariable analysis suggests a significant relationship between adverse events and low DE (patients with DE under median value) (U-HR = 2.59 [1.44–4.64]; p = 0.001. M-HR = 3.16 [1.55–6.46]; p = 0.002); continuous administration (HR = 3.12 [1.65–5.91]; p < 0.001) and WRF (HR = 5.30 [2.79–10.09]; p < 0.001) were also related with adverse events. Conclusions: HD and poor DE are two conditions associated with adverse outcome. Both situations are the consequence of previous detrimental clinical status and they appear strictly related to WRF occurrence.